Nanotechnology in cosmetics: Opportunities and challenges - Silpa Raj; Shoma Jose; U S Sumod; M Sabitha (Wolters Kluwer Medknow Publications, 2012)
Nanotechnology is the science of manipulating atoms and molecules in the nanoscale - 80,000 times smaller than the width of a human hair. The world market for products that contain nanomaterials is expected to reach $2.6 trillion by 2015. The use of nanotechnology has stretched across various streams of science, from electronics to medicine and has now found applications in the field of cosmetics by taking the name of nanocosmetics. This widespread influence of nanotechnology in the cosmetic industries is due to the enhanced properties attained by the particles at the nano level including color, transparency, solubility etc. The different types of nanomaterials employed in cosmetics include nanosomes, liposomes, fullerenes, solid lipid nanoparticles etc. Recently, concerns over the safety of such nanocosmetics are raised and have forced the cosmetic industries to limit the use of nanotechnology in cosmetics and for enforcing laws to undergo a full-fledged safety assessment before they enter into the market. In this review, emphasis is made on the types of nanomaterials used in cosmetics by the various cosmetic brands, the potential risks caused by them both to human life and also to the environment and what all regulations have been undertaken or can be taken to overcome them.